Pendampingan Pengelolaan Pelaksanaan Hari Raya Idul Adha 1443 Hijriyah di Masjid Al-Alif Sangatta Utara - Ramdanil Mubarok; Hendra Bata (Universitas Muhammadiyah Mataram, 2022)
Abstract: This community service aims to assist in managing the implementation of the Eid al-Adha, both managing the Eid al-Adha prayers and khutbah, slaughtering sacrificial animals, as well and job descriptions. The method of implementation is through a meeting of the Al-Alif mosque management, the formation of a committee, setting the agenda, and proposing officers on the implementation of the Eid al-Adha. Furthermore, assisting by being directly involved in the implementation of prayers, khutbah, and slaughtering of sacrificial animals. The service activity ends with monitoring and evaluation. The result is that with this assistance, the implementation of the Eid al-Adha prayer becomes more orderly both at the time of prayer and the khutbah. Similarly, in the implementation of the slaughter of sacrificial animals, the slaughter is carried out by one person, the skinning of the animals is carried out by an expert, the counting and weighing of meat are carried out proportionally, and the distribution of the results of the sacrificial animals is carried out proportionally. qurban meat orderly and on targetAbstrak: Tujuan pengabdian kepada masyarakat ini adalah untuk memberikan pendampingan pada pengelolaan pelaksanaan hari raya Idul Adha, baik pengelolaan pelaksanaan Shalat dan khutbah Idul Adha, pemotongan hewan qurban, serta job description. Metode pelaksanaannya melalui rapat pengurus masjid Al-Alif, pembentukan panitia, penyusunan agenda, dan pengusulan petugas pada pelaksanaan hari raya Idul Adha. Selanjutnya melakukan pendampingan dengan ikut terlibat langsung dalam pelaksanaan shalat, khutbah, dan pemotongan hewan qurban. Kegiatan pengabdian diakhiri dengan monitoring dan evaluasi. Hasilnya adalah dengan adanya pendampingan ini pelaksanaan shalat hari raya Idul Adha menjadi lebih tertib baik pada saat pelaksanaan shalat maupun khutbah. Demikian juga pada pelaksanaan penyembelihan hewan qurban, penyembelihan dilakukan oleh satu orang, menguliti hewan dilakukan oleh ahlinya, pencincangan dan penimbangan daging dilakukan proporsional, serta pendistribusian daging qurban yang tertib, merata dan tepat sasaran.